Corrosion Protection Enhancement using Electropolymerized Aniline Coating on Carbon Steel Pipelines in Industrial Water - Abdulkareem M.A. Al-Sammarrai (Journal of Global Pharma Technology, 2020)
Corrosion of carbon steel in different water system utilities exhibited serious source of financial loses. In this study, electrochemical polymerization of aniline on carbon steel were studied in three types of industrial water (cooling water, waste water and treatment water) as corrosive media. The corrosion parameters; corrosion potential, corrosion current, polarization resistance, corrosion rates, and thermodynamic functions were estimated from Tafel and potentiodynamic procedures at four temperatures; 293,303,313and 323K. Protection enhancements were recorded at all industrial water used in this study and efficiencies of 78-91% were achieved. The results are supported by surface morphology examination before and after coating of carbon steel using atomic force microscope (AFM) and optical light microscopy (OM). Keywords: Electrochemical polymerization, Polyaniline, Nanofibers, carbon steel, Industrial water.